2018
DOI: 10.1002/bip.23118
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of functional properties of a thermostable β‐glycosidase for milk lactose hydrolysis

Abstract: In this work, a new exploitation of the thermostable β-glycosidase from Sulfolobus solfataricus expressed in Saccharomyces cerevisiae to create functional foods for low lactose diets was evaluated. For this purpose, the lactose hydrolysis reaction using immobilized and soluble enzymes was investigated. Activity and stability at different conditions of pH and temperature were tested. The immobilization process had a big impact on the catalysis performance, leading to an enhancement of the enzymatic reaction rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…The recovery of lacS expressed in S. cerevisiae is particularly advantageous since after thermoprecipitation treatments, high degrees of enzyme purification were obtained. As reported by Ionata et al [19], after only two sequential thermoprecipitation steps (at 60 and then 70°C), a 90% recovery of partially pure enzyme with a specific activity of 106 U/mg was obtained; the addition of only one hydrophobic chromatographic step allowed to obtain 2 mg/L of pure enzyme with a specific activity of 166 U/mg [43]. The purification of the enzyme in native form, instead, required three chromatographic steps to separate Sβgly from the archaeal thermostable proteins of S. solfataricus crude extract and yielded only a 28% of enzyme recovery [20].…”
Section: β-Glycosidase Expression In Mesophilic Hosts Expression In Ssupporting
confidence: 55%
See 4 more Smart Citations
“…The recovery of lacS expressed in S. cerevisiae is particularly advantageous since after thermoprecipitation treatments, high degrees of enzyme purification were obtained. As reported by Ionata et al [19], after only two sequential thermoprecipitation steps (at 60 and then 70°C), a 90% recovery of partially pure enzyme with a specific activity of 106 U/mg was obtained; the addition of only one hydrophobic chromatographic step allowed to obtain 2 mg/L of pure enzyme with a specific activity of 166 U/mg [43]. The purification of the enzyme in native form, instead, required three chromatographic steps to separate Sβgly from the archaeal thermostable proteins of S. solfataricus crude extract and yielded only a 28% of enzyme recovery [20].…”
Section: β-Glycosidase Expression In Mesophilic Hosts Expression In Ssupporting
confidence: 55%
“…The efficiency during a biocatalytic process could decrease for the inhibition of increasing concentrations of the product, for the effect on the balance of the reaction, as reported for several galactosidases in the presence of free glucose [58][59][60]. Studies carried out on the Sβgly catalytic efficiency in the presence of large amount of free glucose, used as inhibitor (K i value between 96.7 and 110.4 mM), demonstrated that the monosaccharide did not substantially affect the enzyme affinity and hydrolytic capability for the synthetic and natural substrates [19].…”
Section: Activity Inhibitionmentioning
confidence: 65%
See 3 more Smart Citations